Incorporating egg-transporting pathways into conservation plans of spawning areas: An example of small yellow croaker (Larimichthys polyactis) in the East China Sea zone - Liu, Zunlei; Jin, Yan; Yang, Linlin; Yan, Liping; Zhang, Yi; Xu, Min; Tang, Jianhua; Zhou, Yongdong; Hu, Fen; Cheng, Jiahua (Frontiers in Marine Science, 2022)
Backward-in-time Lagrangian model can identify potential source through reconstructing eggs drifters trajectories, so as to accurately design potential priority conservation for spawning areas. We apply this approach towards the small yellow croaker (Larimichthys polyactis), which is an important commercial species in China. A two-step spatial random forest model is used to predict the occurrence probability and abundance of eggs, and describe the optimal ecological range of environmental factors. Prioritized protection index of the spawning areas is established by combining the optimal occurrence and abundance locations and integrating the backward tracking pathways. The result indicates that the model with environmental variables at time lag of 1 to 2 days show the best explanatory power. Temperature and salinity are the most important factors affecting the eggs occurrence. Furthermore, both of them in the response curve show regime shift, which reflects the fact that parents’ sexual maturation process is physiologically regulated by the ambient environment. The eggs abundance is more correlated with the chlorophyll-a concentration and depth, suggests that parents are more inclined to choose an environment featuring shallow water and high prey to engage in spawning activities. The backtracking of the eggs shows that the potential spawning sources are distributed near the southeast of where the eggs occurred, and the maximum spread distance is no more than 30 km. This finding confirms that the coastal regions of Jiangsu province, which serves as an important spawning ground for small yellow croakers, contributes significantly to the productivity and resilience of this species.